Bakhutli: ancestors returning again, only this time as themselves - Molekoa, Morapeleng (School of Dance, 2025)
How can performance help us remember the past to imagine the future? This study is concerned with the recovery of historical knowledge through performance and the role of an audience in that process. Practice as Research (PaR) is used as a method to identify the role of ancestors in the world of the living. Through autoethnography, I draw examples and insights from my personal experiences with bongaka and my ongoing relationship with my ancestors. In addition, I use performance to enable an engagement between ancestors and the living through ritual process/performance. The ideal of sankofa is employed to frame the research and determine how ancestors could help us remember the past so that we, together with them, could imagine the future. I propose the concept of Bohareng as an alternative consideration of what the future could be viewed as in relation to performance. Performance projects and autoethnographic experiences in the form of field notes are incorporated to arrive at the findings of this study